Physical and biometric characterization of jabuticaba variety 'Pingo De Mel' oriunda of cerrado goiano (Research, Society and Development, 2020)
The biometric and physical characterization can provide information on format, yield, concentration of soluble solids. The objective was to characterize physically and biometrically the jabuticaba variety 'Pingo de mel' from the cerrado of Goiás. 200 jaboticaba were used. The content of total soluble solids, longitudinal and transverse diameters, total mass, volume, shape index, density, yield of peeled pulp and the thickness of the peeled pulp were determined. The total soluble solids 15,16 ° Brix, soluble solids content is one of the most important tools to estimate fruit quality. The longitudinal and transverse diameter was 22.25 and 21.56 mm, respectively. The total mass had an average variation because the coefficient of variation was above 20%. Variations can occur due to cultivation techniques and climate can be related to this also variations presented for the volume of this fruit. As for the format index, the fruit was classified as round. The density was 8.35 g mL -1, yield and pulp thickness were already high. Samples of total soluble solids and yield are parameters used as control and selection by the food industry, it means that the fruits in evaluation presented good potential of industrial processing.